UNRAVELING THE MOTIVATIONAL DRIVE OF MCCANDLESS IN SEAN PENN'S FILM "INTO THE WILD" - Happy Anastasia Usman; Safitri S. Taniyo; Hasna Nurain Mukhsin (Journal of English Language Teaching, Linguistics, and Literature Studies, 2023)
This research studies about the motivation of the main character who chooses to leave his family for free and peaceful life. The objectives of this research is unraveling and exploring McCandless motivation in the movie “into the wild” directed by Sean Penn. The approach used in this research is a qualitative approach with the type of content analysis study. In this cas, psychological analysis is employed. The data are collected through observing the script of the film and take notes. The result of this research shows that there are intrinsic motivation, extrinsic motivation and also there are five types broader motivation that classified into physiological needs, safety needs, love belongingness needs, esteem needs and self-actualization.  Keywords: Film, Main Character, Motivation, Psychology